2001
DOI: 10.1149/1.1376118
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH on Thickness and Ion Content of the Oxide Film on Aluminum in NaCl Media

Abstract: The effect of solution pH on some characteristic properties, i.e., thickness and ion content, of the surface oxide film on high purity aluminum exposed to NaCl solutions have been analyzed by X-ray photoelectron spectroscopy (XPS). The aluminum oxide film thickness is strongly dependent upon the solution pH. In the active dissolution range, i.e., pH <3 and >11, the oxide film is thinner than the native oxide film formed after polishing. Two local maxima were observed at pH ∼3.8 and ∼10.7 where the thickness of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(83 citation statements)
references
References 37 publications
5
78
0
Order By: Relevance
“…Several authors 27,43,[56][57][58]63,67,71,75,76 found Cl − within the oxide film at potentials below E pit and others 46,47 have found Cl − within the oxide film at potentials above E pit . The modeling work by O'Grady et al 79 show Cl − within the oxide and at the oxide metal/interface at potentials below E pit .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several authors 27,43,[56][57][58]63,67,71,75,76 found Cl − within the oxide film at potentials below E pit and others 46,47 have found Cl − within the oxide film at potentials above E pit . The modeling work by O'Grady et al 79 show Cl − within the oxide and at the oxide metal/interface at potentials below E pit .…”
Section: Discussionmentioning
confidence: 99%
“…103 This approach has been used in several studies. 43,67,76 The thickness of the air-formed oxide on Al using XPS was reported to be 4.8 nm by Strohmeier, 103 3.7 nm by Kolics et al 76 and 4.0 nm by Yu et al 67 These Figure 1. pH dependence of chloride adsorption on aluminum ( R is the surface concentration of the radioactive isotope) in 0.1 M NaClO 4 .…”
Section: Oxide Thicknessmentioning
confidence: 93%
See 1 more Smart Citation
“…Amongst these, some studies have been undertaken in weakly acid solution in order to throw light on the effect of pH on the rate of the corrosion process [1][2][3][4][5][6], its inhibition by the addition of organic compounds [7,8], the influence of metal ions [9][10][11] and on the structure of the oxide layer and its semiconductor properties [2]. Electrochemical techniques employed have been mainly open circuit potential (OCP) measurements, polarisation curves and electrochemical impedance.…”
Section: Introductionmentioning
confidence: 99%
“…Polarisation curves [2] and polarisation curves and impedance [3] were used to examine the corrosion behaviour in acetic acid/acetate solutions with a view to controlling the pH near the aluminium surface and gain insight into the corrosion mechanism. The study described in [4] used X-ray photoelectron spectroscopy (XPS) to investigate the influence of pH on the thickness and ion content of the aluminium oxide film in sodium chloride solution. Evidence was found for thicker oxide films at the extremes of oxide stability and the chloride content of the oxide film was maximum at pH 3.8.…”
Section: Introductionmentioning
confidence: 99%